Identity Negotiation of Cina Benteng Community in Building Tolerance - Abdul Malik; Liza Diniarizky Putri; Selly Novinka Putri; Hellya Sri Hartani (Journal of Governance, 2022)
This study aims to examine the negotiation of religious identities within the community of Kalipasir, Tangerang, using data obtained from in-depth interviews of a resident, head of RT and RW. Kalipasir is a religiously divided community, yet there has not been any conflict. The results showed that the negotiation of Buddhist-Confucian identity uses the local language, diverting economic activities with the potential for conflict, tolerance, contributing, and participating in celebrating Islamic rituals. Identity negotiation in the Islamic community is accomplished through ensuring minorities are protected from oppression, avoiding disrupting rituals, utilizing acculturative architecture, and refraining from performing missionary activities. Meanwhile, Christian identity is being negotiated by maintaining distance and only engaging in missionary operations among Buddhist-Confucians. This indicates the assimilationist model attained through communication can be used to build tolerance in Indonesia through multiculturalism.